THE IMPLEMENTATION OF ISLAMIC EDUCATION VALUES IN ENHANCING ENGLISH LEARNING EFFECTIVENESS AT MAKARIMUL AKHLAQ ISLAMIC ELEMENTARY SCHOOL OF JOMBANG - Laily Irmayanti; Hanifudin Mahadun; Khoirotul Idawati; Rofiatul Hosna (Universitas Muhammadiyah Metro, 2025)
Islamic education values have a very important role in shaping the character and behavior of students so that it needs to be implemented in various lines of education, including in English learning. Learning English from an elementary school level has become one of the priorities in education for its crucial role in preparing students for better and higher education and welcoming the challenges of global life in the future. This study examines the implementation of Islamic education values in improving the effectiveness of English learning at Makarimul Akhlaq Islamic Elementary School in Jombang. The research constitutes a case study with qualitative approach in which the researcher gathered data through various methods such as interviews, observations and document analysis to gain a comprehensive understanding of the case.Â It was intended to know hidden meanings, understand social interaction and ensure the validity of data. The results show that the implementation of Islamic values of lifelong education, discipline, and manners in English learning is in the form of varied school programs to build students' motivation in learning, discipline in rules and good manners in speaking English. The implementation of these values has been greatly contributed to enhance English learning to be more effective. This is certainly influenced by environmental factors and teachers who make it easier for students to apply these values in achieving effective and enjoyable English learning. The inhibiting factors are the studentsâ€™ different abilities and characters yet they are successfully overcome by the teachers.Â